Resilience as the organising framework for reform: the dangers of metaphors in financial regulation. Issue 1 (2nd January 2019) - O'brien, Justin
Abstract : As the Global Financial Crisis has demonstrated, fragility without purpose and vigilance is the defining characteristic of any complex system. The tentacles of the finance industry traverse state boundaries. They create moral and economic hazards as well as opportunities. Each poses legitimacy and authority implications. Failure to address those threats have contributed to a populist turn which, in turn, runs the risk of further policy uncertainty and instability. Responding to this crisis through resilience as both metaphor and organising framework is, however, problematic. The paper argues that notwithstanding its increasing usage, resilience is not a neutral concept. Privileging resilience as an end in itself may prove counter-productive unless underpinned by a normative reset of the purpose of the corporation and the market and duties and responsibilities each owe to society. It concludes that without clear definition of purpose and accountability regulatory structural form is irrelevant, as demonstrated by the failure of the twin peak model in Australia.